The Effectiveness of Outdoor-Based Project-Based Learning (PJBL) to Improve School Well-Being in Elementary Schools - Putri, Maylida Adinda; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Current education prioritises student welfare as the central focus in establishing an optimal learning environment. This research endeavours to assess the efficacy of the Outdoor-based Project-Based Learning (PjBL) model in enhancing School Well-being within Elementary Schools. This study adopts a pre-post-test control group design using a quantitative, quasi-experimental methodology. Research instruments are grounded in Allardt’s theory of welfare, encompassing dimensions pertinent to school well-being. The sample comprises 36 fourth-grade students for piloting the School Well-being instrument, with an experimental cohort hailing from Class 5A (31 students) and a control cohort from Class 5B (30 students). Findings reveal a noteworthy disparity between the PjBL and control groups (F=292.588, p < 0.001). Notably, the PjBL group consistently exhibits superior mean scores across all facets of School Well-being, encompassing Having, Loving, Health Status, and Being, relative to the control group. Furthermore, the N-Gain score substantiates a significant divergence: the PjBL group attains 83% (categorised as high), while the control group registers 62% (categorised as medium). These outcomes underscore the efficacy of the outdoor-based PjBL model in ameliorating student learning outcomes. The pragmatic implications of this study underscore the importance of embracing pedagogical approaches that accentuate experiential learning and extracurricular interactions as viable strategies to bolster overall School Well-being and foster student development.